Efficient use of irrigation mineral water in complex therapy parodontitis - M. M. Maschilieva; M. M. Rasulov; M. A. Magomedov (Юг России: экология, развитие, 2015)
165 persons suffering chronic generalized parodontitis (CGP) are surveyed. The medical course irrigation parodontits with mineral water has had positive influence on level of concentration of streptococcal and staphylococcal micro flora in parodontits pockets.